2017
DOI: 10.18632/oncotarget.23086
|View full text |Cite
|
Sign up to set email alerts
|

Survival and time to initiation of adjuvant chemotherapy among breast cancer patients: a systematic review and meta-analysis

Abstract: The relationship between survival and time to the start of adjuvant chemotherapy (AC) among breast cancer patients is unclear. In order to illustrate the effect of delaying the initiation of AC on survival we have undertaken a systematic review and meta-analysis.We identified 12 available studies in the meta-analysis including 15 independent analytical groups. This meta-analysis showed that a 4-week delay before AC was associated with a significantly worse overall survival (OS)(HR=1.13; 95% confidence interval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
50
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(52 citation statements)
references
References 40 publications
0
50
0
Order By: Relevance
“…Time to adjuvant chemotherapy was analysed with three different cut‐off values: within 6 weeks or after more than 6 weeks, within 9 weeks or after more than 9 weeks, and within 12 weeks or after more than 12 weeks. These cut‐offs were chosen based on the currently recommended starting point according to Dutch and ESMO guidelines, and on previous literature demonstrating that a clinical impact is found when adjuvant chemotherapy is started later than 7–12 weeks, indicating the importance of initiating adjuvant chemotherapy at least within this time period.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Time to adjuvant chemotherapy was analysed with three different cut‐off values: within 6 weeks or after more than 6 weeks, within 9 weeks or after more than 9 weeks, and within 12 weeks or after more than 12 weeks. These cut‐offs were chosen based on the currently recommended starting point according to Dutch and ESMO guidelines, and on previous literature demonstrating that a clinical impact is found when adjuvant chemotherapy is started later than 7–12 weeks, indicating the importance of initiating adjuvant chemotherapy at least within this time period.…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have reported that delayed initiation of adjuvant chemotherapy is associated with lower overall and recurrence‐free survival. The recommended acceptable maximum delay, however, varies from 7 to 12 weeks.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Treatment of CMTs is currently limited to surgical removal, as therapy with anticancer drugs has proved largely inadequate . As efficient chemotherapy decreases the risk of breast cancer recurrence and mortality in human patients, an appropriate chemotherapeutic agent might also improve clinical outcomes of tumour resections in dogs. Using CMT cell lines P114 and CF41, we tested whether Palbociclib, a CDK4/6 inhibitor recently approved for treating advanced, ER‐positive mammary tumours in human patients, may represent a candidate for treating CMTs.…”
Section: Discussionmentioning
confidence: 99%
“…Some clinical studies suggest that an adjuvant chemotherapy delay for up to 12 weeks will significantly reduce the effectiveness of systemic therapy. Results of meta-analyses show that OS decreases by 13% and DFS by 14% every four weeks that adjuvant chemotherapy is delayed [28].…”
Section: Discussionmentioning
confidence: 99%